2011
DOI: 10.1186/1746-4811-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of safflower and the efficient recovery of transgenic plants via grafting

Abstract: BackgroundSafflower (Carthamus tinctorius L.) is a difficult crop to genetically transform being susceptible to hyperhydration and poor in vitro root formation. In addition to traditional uses safflower has recently emerged as a broadacre platform for the production of transgenic products including modified oils and pharmaceutically active proteins. Despite commercial activities based on the genetic modification of safflower, there is no method available in the public domain describing the transformation of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…The concentration of A. tumefaciens was also found to be a key factor affecting the transformation frequency (Belide et al 2011;Mishra et al 2013). Previous studies on casuarinas reported that Agrobacterium concentration of OD 600 at 0.1 was used in both C. glauca and A. verticillata transformation (Le et al 1996;Franche et al 1997).…”
Section: Optimization Of the Factors Influencing The Genetic Transformentioning
confidence: 95%
“…The concentration of A. tumefaciens was also found to be a key factor affecting the transformation frequency (Belide et al 2011;Mishra et al 2013). Previous studies on casuarinas reported that Agrobacterium concentration of OD 600 at 0.1 was used in both C. glauca and A. verticillata transformation (Le et al 1996;Franche et al 1997).…”
Section: Optimization Of the Factors Influencing The Genetic Transformentioning
confidence: 95%
“…However, in safflower, genetic engineering until now is confined to vector-mediated (Agrobacterium-mediated) transformation via callus-mediated regeneration (Orlikowska et al 1995;Sankara Rao and Rohini 1999) or embryo transformation (Rohini and Sankara Rao 2000). Belide et al (2011) developed a new protocol for transformation with significant improvements in both the efficiency (about 5 %) and simplicity of implementation over existing safflower transformation protocols. Certainly, safflower is a complex crop to genetically engineer, and many studies describe a series of limitations (Orlikowska et al 1995;Sankara Rao and Rohini 1999) like the lack of genotype-dependent regeneration system, the low efficiency of transformation, the hyper-hydration and necrosis of Agrobacterium-infected cotyledons, the growth retardation of shoots, and the poor rooting and low survival following acclimatization of selected shoots.…”
Section: Transgenic Approachesmentioning
confidence: 99%
“…Moreover, vegetative propagation is efficient because it reduces the amount of time required for seedling establishment and a large number of healthy living stock plants can be produced rapidly from a small amount of available original plant material. Rooted cuttings can also serve as potential rootstocks for grafting experiments for plant species that are recalcitrant to adventitious root induction process or for multiplication of transgenic shoots [8] [9]. In addition, findings on nutrient requirements and effects of auxins on rooting of B. sinuspersici cuttings may provide valuable insight into factors that influence the in vitro regeneration process.…”
Section: Introductionmentioning
confidence: 99%